Драма і театр України в 90-х роках ХХ століття - Барабан, Л. (Студії мистецтвознавчі, 2008)
L. Baraban lightens the peculiarities of the theatrical process in Ukraine in 1990s, analysing activity of the Ukrainian dramatists.